Removal of Subinternal Limiting Membrane Hemorrhage Secondary to Valsalva Retinopathy Using a Fovea-Sparing Internal Limiting Membrane Fissure Creation Technique - Yasuyuki Sotani; Hisanori Imai; Maya Kishi; Hiroko Yamada; Wataru Matsumiya; Akiko Miki; Sentaro Kusuhara; Makoto Nakamura (Case Reports in Ophthalmological Medicine)
Conclusion: Removing foveal sub-ILM hemorrhage without peeling the foveal ILM can be a viable treatment option to preserve the foveal ILM.